Learning style among native Iban students based on their gender in acquiring Malay as a second language - Subramaniam, Vijayaletchumy; Baidin, Batik; Daing Melebek, Abdul Rashid; Yong, Chyn Chye (Canadian Center of Science and Education, 2014)
Most of the teachers pay less focus on students’ learning styles due to their obligation to finish the syllabus within the specified duration, which often resulted in the mismatched of teaching process and learning outcomes. This study aims to identify the different learning styles across gender in acquiring Malay language as a second language among native Iban students in Sarawak. 170 students were chosen from five high schools in Betong region (Sarawak) for analysis, based on the Dunn and Dunn Learning Model (1992). A combination of questionnaire survey and interviews helps to concrete our findings. Results reveal similarities in learning styles across gender in terms of emotional stimulation, psychological, environmental, and physiological factors but differences in sociological stimulation. On the whole, students have deep intrinsic motivation, low desire but positive sense of responsibility, and find it easier to learn Malay language via bonded learning structure compared to liberal ones.